Effectiveness of Acceptance and Commitment Therapy on the Competitive-State Anxiety of warfare victims who are Professional Athletes - Y. Rezapour Mirsaleh; M. Esmaeelbeigi; H. Salari (Afarand Scholarly Publishing Institute, 2019)
Aim: The aim of the present study was to determine the effectiveness of acceptance and commitment Therapy on the competitive-state anxiety of warfare victims who are football athletes in Yazd province. Method: This study was a semi experimental research with two-group and post-pretest and follow up. The population consisted of all warfare victims who are athletes in Yazd province in 2013-2012. By available sampling method, 30 of these athletes were selected and randomly assigned to control and study group (Each group is 15 people). In study group, participants received 8 sessions 120 minutes admission and commitment training and control group received no intervention.  Results: Data collection was performed by the Competitive State Anxiety Questionnaire Martens & et al (1990). Data was analyzed by multiple analysis of covariance (ANCOVA). The findings of ANCOVA analysis showed a significant difference between post-test scores of study and the control groups after the study. In other words, acceptance and commitment therapy resulted in a significant increase (P <0.01) in self-esteem scores and a significant decrease (p <0.01) in physical and cognitive anxiety scores in athletes.This incensement is persistent until follow-up.  Conclusion: Considering the role of levels of anxiety in cognitive and physical functions of athletes, acceptance and commitment therapy can be used to improve self-esteem and reduce physical and cognitive anxiety of warfare victim athletes.